Women talking : a novel - Toews, Miriam, 1964- (New York : Bloomsbury Publishing, 2019)
One evening, eight Mennonite women climb into a hay loft to conduct a secret meeting. For the past two years, each of these women, and more than a hundred other girls in their colony, has been repeatedly violated in the night by demons coming to punish them for their sins. Now that the women have learned they were in fact drugged and attacked by a group of men from their own community, they are determined to protect themselves and their daughters from future harm.
Keywords: Mennonite women -- Fiction; Rape -- Fiction; Misogyny -- Fiction; Conspiracies -- Fiction; Psychological fiction